2005
DOI: 10.1177/08857288050280020501
|View full text |Cite
|
Sign up to set email alerts
|

Description and Evaluation of a University-Based Transition Endorsement Program

Abstract: In this article, the authors describe the implementation and evaluation of a graduate-level transition endorsement program for transition specialists in Ohio. This program was based on the Council for Exceptional Children (CEC) standards for transition specialists that were adopted by Ohio. The Kent State transition endorsement was delivered through four Web-based courses, one on-campus summer course, and a practicum. Competency self-ratings were significantly different pre—post, and program participants indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…However this can be particularly so for young people with an intellectual disability because of the complex pathways and confusing systems that need to be navigated [1,2]. There is a need for coordinated planning, collaboration and decision-making among school staff, families and community agencies [3]. Active student engagement [4] and parental involvement are also critical for a successful transition experience for this population group [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However this can be particularly so for young people with an intellectual disability because of the complex pathways and confusing systems that need to be navigated [1,2]. There is a need for coordinated planning, collaboration and decision-making among school staff, families and community agencies [3]. Active student engagement [4] and parental involvement are also critical for a successful transition experience for this population group [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…First, if service learning is used to enhance preservice teachers' knowledge and skills then they are more likely to have greater confidence in their ability to deliver secondary transition-focused education. Several studies have reported that preservice and inservice teachers are more comfortable around students with disabilities, view abilities of students positively, master related to course content, develop an understanding of the diverse educational needs, and improve service delivery by collaborating with community-based organizations as a result of their engagement in a service learning project (e.g., Flexer & Baer, 2005). Furthermore, preservice teachers may prefer hands-on experiences over hypothetical case studies when gaining requisite transition-related skills.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…The self-assessment contained 19 indicators of state professional teaching standards for highly qualified teachers on a Likert-type scale (1 = very low confidence to 5 = very high confidence ). For content validity, the items were selected to focus on transition-related education aligned with research suggesting the areas of concern new inservice special education teachers experience regarding transition practices (see Flexer & Baer, 2005). Specifically, preservice teachers were asked to rate their confidence in (a) assessing students’ needs, interests, abilities, and problems; (b) using assessment data to plan and use teaching methods; (c) evaluating student progress; and (d) facilitating high school student participation in transition planning.…”
Section: Project Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monk (1994) asserted that, the more classes completed in a particular area during SEPP, the better outcomes teachers could provide for their students in this area. Many researchers have suggested that the failure to address student transition needs and execute best transition practices stems from the lack of special education personnel in transition knowledge and skills (Blalock et al, 2003; Flexer & Baer, 2005). Unfortunately, SEPP often do not have the many competencies necessary for delivering transition-related education and services (Morningstar & Clark, 2003), and research suggests that most secondary special education teachers receive transition training during in-service professional development activities (Greene & Kochhar-Bryant, 2003).…”
mentioning
confidence: 99%